Extended oligo-cyclopentadithiophene dyes for liquid and solid-state dye-sensitised solar cells. Issue 9 (14th April 2022) - Jarusarunchai, Artit; Liu, Xuan; Wu, Wenjun; Robertson, Neil
Abstract : Extended oligo-cyclopentadithiophene dyes show higher electron recombination resistance and a longer electron lifetime. With unusually thin TiO2 of 0.96 μm, high photocurrent density is achieved for ssDSSCs. Abstract : A new series of dyes called T-CPDT, without a strong electron-donor moiety, was designed, based on a combination of previously-reported CPDT and 5T dyes, and synthesised. By addition of a thiophene unit between alkylated CPDT unit(s) and the cyanoacrylic acid acceptor group, their optical, electrochemical and photovoltaic properties were tuned and studied. Upon extending CPDT units from 1 to 3, hence, T-CPDT-1, T-CPDT-2 and T-CPDT-3, the UV-Vis absorption undergoes a bathochromic shift together with a larger extinction coefficient, while the first oxidation potential is less positive. These dyes were applied in DSSC devices with I − / I 3 − electrolyte and with a Spiro-OMeTAD hole transporter. Among the T-CPDT series, T-CPDT-3 shows the highest PCE of 5.88% with I − / I 3 − electrolyte and 4.38% for a solid-state device, mainly due to larger J sc and V oc . Their photovoltaic results with I − / I 3 − electrolyte were compared to those of CPDT-3 and 5T under the same conditions. We also show that the addition of the extra thiophene to CPDT-3, forming T-CPDT-3, leads to slower electron recombination kinetics, compared to those of CPDT-3 and 5T . Interestingly, the solid-state device with T-CPDT-3 achieves a very high J sc of 11.27 mA cm −2 with a less than 1 micron thick TiO2 film which is unusually thin for solid-state devices.